1972
DOI: 10.1121/1.1912868
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Perception. II. Resolution in One-Interval Paradigms

Abstract: This paper reports the results of a series of experiments on tone pulses designed to test certain predictions of the preliminary theory of intensity resolution (Durlach and Braida, 1969) relevant to one-interval paradigms. Resolution was measured in identification and scaling experiments as a function of the range, number, and distribution of intensities, and the availability of feedback. Some of the results, such as those on the dependence of resolution on range and number of stimuli in absolute identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
232
2

Year Published

1983
1983
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(250 citation statements)
references
References 3 publications
16
232
2
Order By: Relevance
“…Preliminary experiments with the full range of curved-line stimuli ( Figure 1, section a) suggested that the selected sampling density (approximately .47-min-arc step size) of reference values of the curvature parameter s in conjunction with range effects was not optimum for revealing possible discrete discrimination performance at low values of the curvature parameter s (compare Braida & Durlach, 1972). Additionally, in three-dot discrimination experiments (Foster, 1979(Foster, , 1982b, discrimination performance was evident over deviations from collinearity corresponding to the first half of the present curvature range.…”
Section: Range Effectsmentioning
confidence: 99%
“…Preliminary experiments with the full range of curved-line stimuli ( Figure 1, section a) suggested that the selected sampling density (approximately .47-min-arc step size) of reference values of the curvature parameter s in conjunction with range effects was not optimum for revealing possible discrete discrimination performance at low values of the curvature parameter s (compare Braida & Durlach, 1972). Additionally, in three-dot discrimination experiments (Foster, 1979(Foster, , 1982b, discrimination performance was evident over deviations from collinearity corresponding to the first half of the present curvature range.…”
Section: Range Effectsmentioning
confidence: 99%
“…Although this approach has certain advantages in accounting for the variability of judgment (Parducci, 1965), subsequent research (Parducci & Perrett, 1971) demonstrated that the effects of various manipulations of the distribution of contextual stimuli were fit better by the present model, which ignores the variability of stimulus representation. Because variations in range have a large effect on the variability of judgment, it can be assumed that the discriminal dispersion for each stimulus is relatively small (Braida & Durlach, 1972;Parducci & Perrett, 1971).…”
Section: Range-frequency Theorymentioning
confidence: 99%
“…Although this approach has certain advantages in accounting for the variability of judgment (Parducci, 1965), subsequent research (Parducci & Perrett, 1971) demonstrated that the effects of various manipulations of the distribution of contextual stimuli were fit better by the present model, which ignores the variability of stimulus representation. Because variations in range have a large effect on the variability of judgment, it can be assumed that the discriminal dispersion for each stimulus is relatively small (Braida & Durlach, 1972;Parducci & Perrett, 1971).The essential idea of range-frequency theory (elaborated in Parducci, 1983) is that the judgment of any particular stimulus represents a compromise between two principles of judgment:(a) The respective categories are assigned to successive, subjec- an equal number of contextual stimuli were assigned to each category while maintaining an ordinal scale); and w is the weighting parameter describing the compromise between the two principles of judgment.In the earliest formulation of range-frequency theory (Parducci et al, I960), the actual values of the numerals printed on the page were used to determine the range values. For example, the numeral 550 was assumed to be at the midpoint of the subjective range of a contextual set of numerals that extended from 100 to 1,000.…”
mentioning
confidence: 99%
“…The discriminability d' is the discrimination index as used in signal detection theory (Green and Swets, 1966 ;Swets, 1973), and has additivity properties made precise by Braida and Durlach (1972 …”
Section: D'(s) = Yh~(wh2eh2(s)) -}-Yke(wkeeko(s)) mentioning
confidence: 99%